KOPERASI SEBAGAI SOKO GURU PENGGERAK EKONOMI PANCASILA - Saputra, Inggar; Saoqillah, Akhmad (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2017)
This paper discusses the economics conception of Pancasila as the strategic value of the five precepts formulated by the founders of the nation. The method in this research is library research. The result of the study is Pancasila economics has the spirit of divinity, humanity, national unity, populist and social justice. The conclusion of this research is Pancasila economics present in the form of Koperasi as "soko guru" which aim to realize prosperity of Indonesian people. Keywords: economic of Pancasila, koperasi